Pharmacotherapy and nutritional supplements for seasonal affective disorders: a systematic review. (24th July 2018) - Cools, Olivia; Hebbrecht, Kaat; Coppens, Violette; Roosens, Laurence; De Witte, Andy; Morrens, Manuel; Neels, Hugo; Sabbe, Bernard
ABSTRACT: Introduction : A seasonal affective disorder (SAD) is a subtype of unipolar and bipolar major depressive disorders. It is characterized by its annual recurrence of depressive episodes at a particular season, mostly seen in winter and is responsible for 10–20% of the prevalence of major depressive disorders. Some pathophysiological hypotheses, such as the phase delay and the monoamine depletion hypotheses, have been postulated but the exact cause has not been fully unraveled yet. Studies on treatment for SAD in the last decade are lacking. To tackle this chronic disease, attention needs to be drawn to the gaps in this research field. Areas covered : In this systematic review, the authors give a broad overview of the pharmacological therapy available for SAD. Also, nutritional substances fitting well with the postulated hypotheses are reviewed for the treatment and prevention of SAD. There is a specific focus on the quality of the currently performed studies. Expert opinion : Light therapy and fluoxetine are the only proven and effective acute treatment options for SAD, while bupropion is the only registered drug for prevention of SAD. This area of research is in dire need of valid large-scale and sufficiently reproducible randomized control trials.